(untitled) (Journal of Economic Research & Business Administration, 2018)
The modern economy is called the economy of the effective human capital, which emphasizes its main role in the development of the economy and society as a productive factor. Human capital becomes the most important factor in the economic growth of the country, the basis of sustainable economic development. The relevance of scientific research is due to the fact that the effectiveness of the use and development of human capital is the main priority for most of the leading countries of the world. The article considers approaches to the definition of the concept and the theoretical content of the category of human capital, its importance for the development of areas of science and practice. It is shown that human capital is a necessary independent factor determining economic growth. The necessity of reflecting human capital in the accounting and reporting system of firms is substantiated. The main problems of recognition of this most important factor of production are identified, and directions for their further solution are defined. The scientific and practical necessity of introducing a new object of accounting and analysis of human capital has been substantiated. The possibility of adequate accounting and assessment, as well as a reliable reflection of the intellectual potential of the company in the financial statements is a necessary condition for the formation of its fair value. The article contains information and conclusions that have practical interest for firms.